The Measurement of the Noise Level Based on Roads Classifications in Urban Area (Case Study: Harjamukti, Depok) - Hanaseta N., Evelyne; Laila Febrina (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2023)
Harjamukti Village is located in Depok City which is a buffer zone for the capital city of DKI Jakarta, the rapidly growing housing sector shows that this location has an attractiveness. The next problem that arises is the potential for noise from vehicular traffic due to community mobility. Noise measurements carried out using SNI 8427: 2017 show the LSM value on each road: Tumaritis Road (68.87 dBA), Bungur Road (61.29 dBA), Putri Tunggal Road (73.67 dBA), Putri Tunggal District Road (65.7 dBA) and Sementara Road (61.29 dBA). This study was conducted to see the road class based on the noise and capacity parameters, so that from these two parameters, can we clearly show the road class being analyzed. The measurements were carried out for 24 hours using the standard SNI 8427: 2017. The quality standard for the residential area used was 55 Dba based on the Minister of Environment Decree No. 48 of 1996. The road capacity used is analyzed based on the number of vehicles and the class of each road. Based on the noise parameters (sig 0.006) and capacity (sig 0.000) so that from the noise parameter there is no significant difference in the 5 research locations, while the road capacity shows a significant difference from the 5 research locations. Prediction of road class cannot be determined from the noise value and road capacity, because the noise obtained needs to be analyzed for the types of activities around whether there is an influence from other activities that are also dominant, such as toll roads and road capacity, because there are local road classes whose capacity is not detected different from collector road class.